English Syllabus Development: A Need Analysis-Based Approaches - Ikrama Prasetya; Djatmika; Ngadiso (South Sulawesi Education Development (SSED), 2025)
This study investigates the English language skills required by students at Aviation Vocational High Schools, focusing on syllabus development and the challenges teachers face in preparing effective teaching materials. The research aims to identify the necessary English skills for aviation students, explore the difficulties in syllabus creation, and determine the skills teachers need to design a relevant curriculum. A needs analysis approach was used, with data collected through questionnaires, interviews, and document analysis of the existing syllabus. The study found that speaking skills were the most crucial, followed by reading, listening, and writing. However, the current syllabus does not adequately meet the needs of students, as teachers face challenges such as the lack of diagnostic assessments and materials that are not aligned with aviation industry standards. The study also identifies key teacher skills necessary for effective syllabus development, including the ability to assess student needs and ensure the syllabus is implemented in a way that aligns with the intended learning objectives. The findings highlight the need for a more tailored and effective approach to syllabus design in aviation vocational education.